Ernst von Stern über Catilina und die Gracchen - von Ungern-Sternberg, Jürgen (Hyperboreus, 2016)
The specialist for ancient history and classical archeology Ernst von Stern (1859–1924) of Baltic origin studied at the universities of Leipzig and Dorpat (Tartu). He became professor at the university of Odessa in 1886 and in 1911 at the university of Halle. He died during his second rectorship in Halle in 1924. The article deals with his archeological excavations in Southern Russia and his essays about problems of his own time during and after the First World War. But in the ﬁrst place it deals with von Stern’s two essays about some important ﬁgures of the late Roman republic: his thesis in Dorpat about Catilina in 1883 and his article about the Gracchi in 1921. Whereas his thesis is a good study of the ancient sources with only cursory remarks on his own time, von Stern’s article about the Gracchi bears the imprint of the Russian revolutions of 1905 and 1917/18. That enables him to understand better some features of the Gracchan crisis, especially the revolutionary turn of the year 133 BC.